Oxygen Electroreduction on Zinc and Dilithium Phthalocyanine Modified Multiwalled Carbon Nanotubes in Alkaline Media. Issue 6 (1st January 2017) - Türk, Karl-Kalev; Kaare, Kätlin; Kruusenberg, Ivar; Merisalu, Maido; Joost, Urmas; Matisen, Leonard; Sammelselg, Väino; Zagal, José H.; Tammeveski, Kaido
Abstract : Dilithium and zinc phthalocyanine derived catalysts supported on multiwalled carbon nanotubes (MWCNTs) have been studied as non-precious metal catalysts for oxygen electroreduction. The electrocatalysts were prepared by simple pyrolysis by varying the pyrolysis temperature and metal phthalocyanine-to-MWCNT ratio. The surface morphology of the catalyst materials was characterized by scanning electron microscopy (SEM) and surface composition by X-ray photoelectron spectroscopy (XPS). The rotating disk electrode (RDE) method was used to determine the electrocatalytic activity of these materials in 0.1 M KOH solution. The oxygen reduction reaction (ORR) activities achieved are comparable to well-studied Fe and Co phthalocyanine based catalysts in alkaline media, showing the great potential of non-redox-active metal phthalocyanine-derived catalysts as cathode materials for metal-air batteries and fuel cells. The number of electrons transferred per O2 molecule was determined by the Koutecky-Levich analysis, which indicated that at high negative potentials the ORR process followed a four-electron pathway. The O2 reduction results obtained in this study show clearly the important role of non-redox-active metal ion in the formation of active sites for ORR on pyrolyzed and carbon supported Li and Zn metallomacrocyclic compounds.